SOCIO-ECONOMIC DEVELOPMENT IN PUNJAB: THIRD TERM OF SHEHBAZ SHARIF AS CHIEF MINISTER - Dr. Asim Niaz Khan; Nisar Ali Shah; Sher Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
This research work has been carried out in order to assess the socio-economic development in Punjab province after general elections of 2013. It was record third time that Shehbaz Sharif of Pakistan Muslim League Nawaz (PMLN) became the Chief Minister. Shehbaz Sharif has been commonly praised for his untiring efforts in the governance spheres. According to the experts and analysts, the record victory of PMLN in general elections of 2013 fruit of Shebaz Sharif`s rigorous administrative performance in Punjab during 2008-2013. This study is qualitative in nature where the primary data was collected from the archives, official record, statements of the government officials and official websites. Secondary data was gathered from research articles, newspapers, and journals. Content analyses has been utilized for analysis of gathered data to answer the research questions. After careful consideration and analyses of data, the researchers have reached to the conclusion that Shehbaz Sharif has significantly contributed to the socioeconomic development of Punjab during his 3rd term as Chief Minister of Punjab. The results and conclusions of the research are also evident in public opinions where Shehbaz Sharif has been scored high amongst all the four Chief Minister of Pakistan.